O videoclipe brasileiro pelo viés do Manguebeat : a contribuição do diretor - Duarte, Fernanda Carolina Armando (2011)
This research aims to salvage and registry a media still rarely studied in Brazil, because this was almost always seen as a smaller media, or just a branch of the commercial video, and the study of the director's role within this work. The role of music video director, unlike film director, is several times relegated to the background or ignored by the media and public, linking directly to the band's work, forgetting that there is an author. Still, several years ago, the video has acquired a higher status with the evolution of their language and able to unite the art trade, in order to make the band portrayed retains its personality and work of the director can show his signature in the work, and be received extremely positive, especially for youth. Leveraging the Manguebeat is a broad movement that proposes the development through dialogue with the traditions and diversity, based on Brazilian culture, we believe appropriate to talk of the music video with Brazil against the backdrop of this universe. For this, we intend to study the work of two directors: Raul Machado and Gringo Cardia, as well as the historical and ideological implications of the movement Manguebeat, and from this analysis, to confront the vision of each of the directors before the movement, through the look that they portrayed in their music videos Manguetown (Gringo Cardia - 1996) and Maracatu Atômico (Raul Machado - 1996), performing a thorough analysis of the works, and compare them to some impressive music videos of the time.